GENDER STEREOTYPES IN ETAF RUMâ€™S â€œA WOMAN IS NO MANâ€ NOVEL (Sastra Inggris UNPAM, 2022)
The aim of this study is to analyse gender stereotypes and how the main character deal with it that is portrayed in the novel entitled A Woman is No Man by Etaf Rum. This study uses the qualitative approach by describing and analysing the characters in the novel. In order to analyse the data, the writer uses theory of gender performativity (Butler, 1999). The result of this study shows the analysis of gender stereotypes on how male and female bodies are differentiated through certain standards of appearance, personality traits, also responsibility that are considered appropriate for both genders. It also describes that the main character can deal with the gender stereotype by understanding herself to take opportunity for growth. Through analysing this study, it concluded that female and male bodies identified being feminine and masculine as they performed certain acts and attributes purpose for female and male.Keywords: Gender Stereotypes, Feminine, Masculine, Novel.